Proton-Beam Therapy for Hepatocellular Carcinoma Associated with Portal Vein Tumor Thrombosis - Sugahara, Shinji; Nakayama, Hidetsugu; Fukuda, Kuniaki; Mizumoto, Masashi; Tokita, Mari; Abei, Masato; Shoda, Junichi; Matsuzaki, Yasushi; Thono, Eriko; Tsuboi, Koji; Tokuuye, Koichi (Strahlentherapie und Onkologie, 2009)
Background and Purpose: The prognosis of patients with advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombosis (PVTT) is extremely poor, as effective treatment options are limited. The authors performed a retrospective review to evaluate the efficacy of proton-beam therapy (PBT) for patients presenting with PVTT in the setting of HCC. Patients and Methods: Between February 1991 and September 2005, 35 patients with HCC and tumor thrombi in the main trunk or major branches of the portal vein presented for consideration of PBT. Their tumor sizes ranged from 25 mm to 130 mm (median, 60 mm). A median total dose of 72.6 GyE in 22 fractions was delivered over 31 days to a target volume that encompassed both the primary hepatic lesion and the PVTT. Results: 32 patients were progression-free during a median follow-up period of 21 months (range, 2–88 months) and three patients experienced disease progression. Local progression-free survival rates were 46% at 2 years and 20% at 5 years, and the median local progression-free survival was 21 months. Acute toxicity ≥ grade 3 was observed in three patients, and no patient experienced late toxicity ≥ grade 3. None of the patients had to discontinue treatment as a result of toxicity. Conclusion: PBT improved local control and significantly prolonged survival in HCC patients with PVTT.